Where do we go with HIV pre-exposure prophylaxis in Indonesia? - I Nyoman Sutarsa (Public Health and Preventive Medicine Archive, 2017)
PrEP is an effective additional prevention strategy at trial settings. Decision to adopt PrEP as a public health intervention must be made based on the need and capacity of current systems. Instead of allocating substantial resources for PrEP, the limited resources could be wisely allocated to scale-up the existing prevention strategies including access to ART, as well as to ensure equality of access of people to full-range of HIV prevention and treatment measures.